Inside High-Rise Housing Securing Home in Vertical Cities - Nethercote, Megan (Bristol University Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Condominium and comparable legal architectures make vertical urban growth possible, but do we really understand the social implications of restructuring city land ownership in this way? Geographer and architect Megan Nethercote enters the condo tower to explore the hidden social and territorial dynamics of private vertical communities. Informed by residents' accounts of Australian high-rise living, this book shows how legal and physical architectures fuse in ways that jeopardize residents' experience of home and stigmatize renters. As cities sprawl skywards and private renting expands, this compelling geographic analysis of property identifies high-rise development's overlooked hand in social segregation and urban fragmentation, and raises bold questions about the condominium's prospects.